Application of shelter as feeding plate with different combination of diatom species in the rearing of juvenile sea cucumber, Stichopus horrens - Sembiring, Sari Budi Moria; Giri, Nyoman Adiasmara; Hutapea, Jhon Harianto; Mahasetiawati, Ni Ketut; Gunawan, Gunawan; Setiadi, Ananto; Hendrawan, Sudira (Penerbit Universiti Kebangsaan Malaysia, 2025)
The cultivation of Stichopus horrens, a sea cucumber with high economic value, requires further development. This study investigates the effect of incorporating shelters that function as feeding plates on the growth and survival of juvenile sea cucumbers by enhancing food availability and accessibility. The study was conducted for two months using 12 rectangular polycarbonate tanks in a completely randomized design with four treatments and three replications. The experiment consisted of the treatments: (A) feeding plate containing Chaetoceros muelleri and Navicula sp.; (B) feeding plate containing C. muelleri and Nitzschia sp.; (C) feeding plate containing C. muelleri, Navicula sp., and Nitzschia sp.; and (D) no feeding plate, but all three diatom species were added directly to the rearing tank. Each tank was stocked with 100 juveniles with an average length and weight of 0.64 ± 0.14 cm and 0.06 ± 0.01 g, respectively. Parameters observed included growth, survival, grazing on the feeding plate, and digestive enzyme activity. The growth of juveniles in treatments A and C was higher and significantly different from treatments B and D (p<0.05). The highest survival was obtained in treatment C of 67.0 ± 7.02%, significantly different from treatments B (p < 0.05). The results of the present study indicate that the growth of sea cucumber juveniles is enhanced under rearing conditions with the addition of shelters. Furthermore, the presence of Navicula sp. significantly accelerates both growth and survival rates in juveniles.